SOCIO-PSYCHOLOGICAL RECORD OF SOUTHERN THAILAND WOMEN: A STUDY ON THE POLITICAL CONFLICTS 1903-2014 OF SOUTHERN THAILAND - Baboe, Kuwing; Rajab, Khairunnas (Jurnal Syariah, 2017)
This is a qualitative study which prioritizes the use of inductive logic in which the categorization and meaning of symptoms, or the construction of reality are derived from a direct interview with women from Southern Thailand. Qualitative research is characterized as a depiction of reality found through interviews specifically in this regard with 340 women, by a snowball sampling technique, which collects data from respondents. It was conducted by interviewing recommended respondents from Thai society who understand the socio-psychological condition of Pattani, Yala, and Narathiwat in order to verify the theory and socio-psychological phenomenon. This research adopts a qualitative method; a descriptive study to assess the impact of the political conflicts in Southern Thailand on its women’s sociopsychological conditions. To achieve this goal, researchers sought to analyze, interpret and construct facts, symptoms and events through detailed descriptions and understand meanings contained in socio-psychological conditions of Southern Thailand women. In order to obtain accurate data, the researchers conducted indepth interviews to identify what really happens based on strict scientific rules and principles on women’s socio-psychological condition in encountering political conflict. Southern Thailand women are considered weak and unfit for political activities. This image brings negative effects on development of the sociopsychological condition of the women. They cannot work outside, and as a result, they spend much more time with domestic affairs. They even suffer from stress, depression, psychosis, and psycho neurosis. These women suffer from prolonged trauma due to hostility, conflict, bombings, murder and terrorist acts. Political conflict in Southern Thailand continues endlessly. It makes the social order damaged, interaction disturbed, and domestic violence and divorce rates rise. The conflict harms the mental condition of all parties. However, women suffer more than men do. To ease the conflict, attention to social and psychological aspects should be taken into account. There should be no discrimination of gender. Also, religious leaders, academics, government, and neutral third parties should collaborate to ease the conflict.